ATTITUDES TOWARD STATISTICS AND ACHIEVEMENT: BETWEEN STUDENTS OF SCIENCE AND SOCIAL FIELDS - Dian Cahyawati; Wahyudin Wahyudin; Sufyani Prabawanto (Jurnal Infinity, 2018)
The purpose of this study was to explore students' attitudes toward statistics (ATS) based on the beginning and the end of learning, based on differences in fields of study, and examine its relationship with statistical acheivement. ATS was measured by an attitude instrument, namely The Survey of Attitudes toward Statistics (SATS) which consists of six dimensions (affective, cognitive competence, difficulty, value, interest, effort). Research respondents were undergraduate students who took lectures on statistical recognition that came from at one of the universities in South Sumatra. The results of the descriptive analysis showed the variation of ATS in each dimension of attitudes classified into positive, neutral, or negative attitudes. Although there are variations in the response of student attitudes in each dimension, but the results of statistical tests have not been able to show differences in attitudes between the beginning and the end of learning in each dimension. The differences in attitudes between the beginning and the end of learning that are statistically significant are in the dimensions of affective, value, and effort. The difference in the field of student science shows the difference in ATS, but only in the dimension of value. This study does not have enough evidence to state that there is a significant relationship between student attitudes to statistics and the results of learning statistics.